2019
DOI: 10.1186/s12935-019-0805-2
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between ER stress and mitochondrial pathway mediated adriamycin-induced testicular toxicity and DA-9401 modulate adriamycin-induced apoptosis in Sprague–Dawley rats

Abstract: Background DA-9401 was prepared as a mixture of Chinese medicinal herb extracts from roots of Morinda officinalis How (Rubiaceae), outer scales of Allium cepa L. (Liliceae) and seeds of Cuscuta chinensis Lamark (Convolvulaceae). The present study was designed to investigate the possible protective role of DA-9401 in adriamycin (ADR)-induced testicular toxicity associated with oxidative stress, endoplasmic reticulum (ER) stress, and apoptosis. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 42 publications
(65 reference statements)
4
49
0
Order By: Relevance
“…Human clinical trials are necessary for a precise understanding of what the health benefits of noni juice might be. Human intervention studies also indicate that noni juice may improve joint health, increase physical endurance, increase immune activity, Blood Lipid Normalization, hs-CRP and Homocysteine Reduction, Control of Advanced Glycation End Products (AGEs) and Glycosylated Hemoglobin, inhibit glycation of proteins, aid weight management, help maintain bone health in women, help maintain cancer and rheumatoid arthritis, help maintain normal blood pressure and Mitigation of Osteoporosis, and Gingivitis and improve gum health [35][36][37][38][39][40][41][42][43][44][45][46][47][48] . It has shown for the first time in the literature that serum ADMA levels from endothelial dysfunction markers have decreased and FMD has increased with the use of these three products, and especially with the effect of noni fruit, which is known for its anti-atherosclerotic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Human clinical trials are necessary for a precise understanding of what the health benefits of noni juice might be. Human intervention studies also indicate that noni juice may improve joint health, increase physical endurance, increase immune activity, Blood Lipid Normalization, hs-CRP and Homocysteine Reduction, Control of Advanced Glycation End Products (AGEs) and Glycosylated Hemoglobin, inhibit glycation of proteins, aid weight management, help maintain bone health in women, help maintain cancer and rheumatoid arthritis, help maintain normal blood pressure and Mitigation of Osteoporosis, and Gingivitis and improve gum health [35][36][37][38][39][40][41][42][43][44][45][46][47][48] . It has shown for the first time in the literature that serum ADMA levels from endothelial dysfunction markers have decreased and FMD has increased with the use of these three products, and especially with the effect of noni fruit, which is known for its anti-atherosclerotic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in vitro study in mouse Leydig MTTC-1 cell reported ER stress mediated apoptosis by upregulation of ER stress proteins PERK, EIF2α and ATF4; ER stress apoptosis-relative proteins caspase-3, caspase-7 and caspase-12, and autophagy protein microtubule-associated protein 1A/1B-light chain 3 (LC3II) and autophagy related 5 (Atg5) suggest ER stress mediated apoptosis and autophagy are the mechanism involved in spermatogenic dysfunction [75]. Recent study from our lab reported adriamycin-induced testicular dysfunction by the crosstalk between ER stress and mitochondrial mediated signaling pathway [76]. Another commonly used chemotherapy drug busulfan-induced apoptosis in both testicular germ cells in mouse and C18-4 cell line by upregulation of IRE1 and PERK pathway [77].…”
Section: Involvement Of Endoplasmic Reticulum Stress In Testis and Gementioning
confidence: 99%
“…Stress-induced testicular dysfunction and corresponding pathological features have been well documented in rats [26]. MOTILIPERM has been used as an antioxidant to reduce lipid peroxidation, scavenge free radicles, and prevent germ cell apoptosis in varicoceles and drug-induced testicular toxicity [19,20,[23][24][25]. The present study reported for the first time the effect of MOTILIPERM on reproductive parameters in immobilization stress-induced male infertility in adult SD rats.…”
Section: Discussionmentioning
confidence: 62%
“…Quercetin 4 -O-glucoside and quercetin is the predominant compound present in Allium cepa L. (Liliaceae) outer scales, which has antioxidant and androgenic effects [22]. Recently, we found that MOTILIPERM has a beneficial effect on spermatogenesis after cisplatin, adriamycin, and finasteride treatment in rats [23][24][25]. Administration of MOTILIPERM can increase germ cell proliferation by protecting the testis from oxidative stress, endoplasmic reticulum (ER) stress, and mitochondrial-mediated apoptosis [19,23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation